The Annual Conference of Lithuanian Society of Paediatric Surgeons. The Abstract Book - Pikturnaitė, Gabija; Dagilytė, Rūta Vilija; Verkauskas, Gilvydas (Vilnius University Proceedings, 2025)
Lithuanian Society of Paediatric Surgeons was founded in 1994 and organises conference annually. The first conference after the presidency returned to Vilnius University Hospital Santaros Klinikos was dedicated to multisystem trauma as a leading cause of paediatric mortality. Reports from most centres of paediatric surgery were presented together with invited lectures on head trauma, maxillofacial surgery, trauma team activation protocol, war medicine and legal aspects of paediatric surgery. The Abstract Book includes reports on the most complicated cases encountered by paediatric surgeons recently.